Etika Sains Dalam Perspektif Islam - jumadi, Muhammad; Nisa hasanah; Rifauzi juliandani (Mataram University, 2024)
Although science and Islam have different perspectives, it is important to increase alignment between the two. These two elements play a vital role in human life and the progress of a nation. Religion functions as a guide or guidance through rules in the holy books, while science (science) focuses on communicative interactions in society. The two naturally have an integrated relationship in terms of behavior, morals, ethics and social life